Combination leflunomide and methotrexate in refractory rheumatoid arthritis: a biologic sparing approach. (October 2016) - Hodkinson, Bridget; Magomero, Kingsley Ross; Tikly, Mohammed
Background: In resource-constrained settings where biologic agents are not widely available, there are limited therapeutic options for patients with rheumatoid arthritis (RA) refractory to other synthetic disease modifying antirheumatic (DMARD) therapies. The aim of this study is to evaluate the effectiveness and safety of leflunomide (LEF) with methotrexate (MTX) in refractory RA. Methods: A retrospective record review of adult RA patients treated with LEF/MTX. Demographic details, adverse reactions, and the 3-variable 28 joint disease activity score (DAS28-3) were recorded at initiation of LEF/MTX therapy, and after 4 and 12 months of treatment. Results: Of 194 patients, most were middle-aged seropositive Black African females, with established disease [mean (standard deviation, SD) disease duration 9.4 (8.2) years] and time on previous DMARDs of 7.0 (5.5) years. Before adding LEF, the mean (SD) dose of MTX was 21.7 (3.5) mg/week, and 87.6% of patients used low dose oral corticosteroids. A good or moderate EULAR response was achieved by 44% and 42% of patients, and the retention rate was 71%. Major infections were seen in 6 patients: comprising 2 deaths, 3 cases of leucopaenia and septicaemia and 1 case of tuberculosis. Hepatotoxicity ( n = 3), intolerable gastrointestinal symptoms ( n = 3), and hypertension ( n = 17) were the most common problems. Predictors of remission or low disease activity at 12 months was a baseline DAS28-3 ⩽ 5.5 [odds ratio (OR) = 2.7; 95% confidence interval (CI) 1.1–5.6; p = 0.01]. Conclusions: LEF/MTX was effective in the majority of patients in this cohort of mainly Black African women who failed other combination synthetic DMARDs, particularly in those with moderate disease activity at the time of addition of LEF. Infections and hypertension were important complications. In a setting where biologic DMARDs are not readily accessible, the combination of LEF/MTX is a cost-effective approach.